2022
DOI: 10.3390/foods11203160
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Linalool against Shigella sonnei and Its Application in Lettuce

Abstract: Shigella sonnei (S. sonnei) infection accounted for approximately 75% of annual outbreaks of shigellosis, with the vast majority of outbreaks due to the consumption of contaminated foods (e.g., fresh vegetables, potato salad, fish, beef, etc.). Thus, we investigated the antibacterial effect and mechanism of linalool on S. sonnei and evaluated the effect of linalool on the sensory quality of lettuce. The minimum inhibitory concentration (MIC) of linalool against S. sonnei ATCC 25931 was 1.5 mg/mL. S. sonnei was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This may be a result of the action of ethylene oxide on the cellular tissues of the fruit, which may undergo structural changes that directly affect the firmness of the fruit. The results of Su et al [65] suggested that the addition of linalool may lead to a change in the pH of the soaking solution, which alters the changes in the texture of the lettuce leaves. Linalool may also react with damaged material in freshly cut leaves, leading to changes in sensory quality.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a result of the action of ethylene oxide on the cellular tissues of the fruit, which may undergo structural changes that directly affect the firmness of the fruit. The results of Su et al [65] suggested that the addition of linalool may lead to a change in the pH of the soaking solution, which alters the changes in the texture of the lettuce leaves. Linalool may also react with damaged material in freshly cut leaves, leading to changes in sensory quality.…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, it has also been demonstrated that linalyl alcohol can exhibit excellent antimicrobial activity against a wide range of food-contaminating bacteria such as Shewanella putrefaciens, Pseudomonas aeruginosa, and Shigella [22][23][24]. But fewer studies have been conducted on how linalyl alcohol prevents B. thermosphacta.…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier studies have suggested that it can harm cell membrane integrity, produce macromolecules and intracellular enzyme efflux, avert protein synthesis, and impede cellular metabolism [22,23]. Additionally, linalyl alcohol can increase the membrane lipid oxidation-induced hyperpolarized cell membrane potential, decrease intracellular adenosine triphosphate (ATP) levels, and increase intracellular reactive oxygen species (ROS) concentrations [23][24][25][26]. As a result, the current work attempts to improve the antibacterial mechanism of linalyl alcohol by testing its disruptive and inhibitory effects on DNA, intracellular chemicals, and Brochothrix thermosphacta as a research topic.…”
Section: Introductionmentioning
confidence: 99%